15 PROTECTIVE EFFECTS OF OXIDIZED PHOSPHOLIPIDS ON VENTILATOR-INDUCED LUNG INJURY. (1st March 2006) - Burdette, D. O.; Nonas, S. A.; Miller, I.; Birukova, A. A.; Chatchavalvanich, S.; Garcia, J. G.N.; Birukov, K. G.
Abstract : Purpose of Study: Acute lung injury (ALI) is a devastating syndrome characterized by pulmonary inflammation and vascular barrier dysfunction with protein-rich edema. Mechanical ventilation at high tidal volumes can worsen existing ALI and even cause ventilator-induced lung injury (VILI) de novo. Previous studies have demonstrated that oxidized 1-palmitoyl-2-arachidonoyl- sn -glycero-3-phosphorylcholine (OxPAPC) enhances basal endothelial cell (EC) barrier properties and prevents acute lung inflammation and EC dysfunction in response to bacterial lipopolysaccharide (LPS) via direct Rac-Cdc42-mediated effects on EC cytoskeleton and via competitive inhibition of LPS binding to toll-like receptor 4 (TLR4). Methods: Adult male Brown Norway rats (250-350 g) were ventilated at low tidal volume (LTV, 7 mL/kg) or high tidal volume (HTV, 20 mL/kg) for 2 hours, 85 breaths/min. A subset of animals received intravenous OxPAPC (1.5 mg/kg) at the start of mechanical ventilation. Bronchoalveolar lavage (BAL) cell count and protein concentration were measured as markers of inflammation and vascular permeability. IL-6, IL-1beta, and hyaluronan levels in BAL were quantitatively assessed by enzyme linked immunoabsorbance assays (ELISA). Results: HTV caused a 70% increase in BAL total cell count ( p < .05) and a 169% increase in BAL protein (p < .01) compared with controls. OxPAPC reduced HTV-induced elevations in total cell count (41% decrease versus HTV alone) and protein (42% decrease versus HTV alone). HTV also caused an increase in the hyaluronan levels found in BAL samples, which was completely abrogated by intravenous injection of OxPAPC. HTV also caused a 223% increase in the IL-6 levels in BAL samples as compared to controls, which was attenuated by OxPAPC treatment (130% versus control, p < .05). HTV had only a modest effect on IL-1beta up-regulation (45% increase versus control), which still was attenuated by OxPAPC treatment (27% increase versus control). Conclusion: These studies demonstrate for the first time the protective effect of membrane-derived oxidized phospholipids on ventilator-induced lung inflammation and barrier dysfunction. HL75349, HL76259, HL58064.